ASSESSMENT OF URBAN LAND USE AND ENVIRONMENTAL SENSITIVE AREA DEGRADATION IN AKURE, NIGERIA USING REMOTE SENSING AND GIS TECHNIQUES - Olajuyigbe, Ayo Emmanuel; Adegboyega, Suleiman Abdul-Azeez; Popoola, Olusola Olalekan; Olalekan, Olabode Abiodun (European Scientific Journal, ESJ, 2015)
The use of satellite imageries and spatial analysis techniques have not been comprehensively explored and exploited in capturing baseline information for monitoring of ecologically fragile areas in most developing countries including Nigeria. This study used Landsat imageries of Akure 1986, 2002 and 2011, and topographical map, DEM, GPS points, mean annual rainfall data and structured questionnaire. Image classification was performed using supervised classification technique to capture the urban land use change over the study period. The wetlands were buffered to the radius of 200m to select the target population for questionnaire administration using ArcGIS 9.3. The responses obtained were analyzed using SPSS 17.0. DEM was subjected to spatial analysis using spatial analyst extension of the ArcGIS 9.3 and Global Mapper 13 to identify the watersheds, generate flow direction, flow accumulation and to generate the basin levels. The mean annual rainfall data, drainage basin data and elevation data were integrated and reclassified. These data were subjected to multi-criteria analysis and map overlay operation to generate flood vulnerability index map. The finding observed that area with high vulnerability to flooding occurred along the streams or river channels flowing from the eastern region of the study area towards the northwest region where physical planning standards especially on setbacks were compromised.